Pan-Cancer Analysis Reveals a Distinct Neutrophil Extracellular Trap-Associated Regulatory Pattern - Shen, Xiao-Tian; Xie, Sun-Zhe; Xu, Jing; Yang, Lu-Yu; Qin, Lun-Xiu (Frontiers in Immunology, 2022)
Background Neutrophils form extracellular net-like structures called neutrophil extracellular traps (NETs). Emerging evidence has shown that cancer can induce NETs formation; however, it is not fully understood how NETs influent cancer biology, and no consensus has been reached on their pro- or anti-tumor effects. A comprehensive analysis of the global NETs-associated gene regulatory network is currently unavailable and is urgently needed. Methods We systematically explored and discussed NETs enrichment, NETs-associated gene regulatory patterns, and the prognostic implications of NETs in approximately 8,000 patients across 22 major human cancer types. We identified NETs-associated regulatory gene sets that we then screened for NET-associated regulatory patterns that might affect patient survival. We functionally annotated the NETs-associated regulatory patterns to compare the biological differences between NETs-related survival subgroups. Results A gene set variation analysis (GSVA) based on 23 major component genes was used to calculate a metric called the NETs score. We found that the NET score as closely associated with many important cancer hallmarks, particularly inflammatory responses and epithelial-to-mesenchymal transition (EMT)-induced metastasis. Higher NETs scores were related to poor immunotherapy response. Survival analysis revealed that NETs had diverse prognostic impacts among various cancer types. The NETs-associated regulatory patterns linked to shorter or longer cancer patient survival were distinct from each other. Functional analysis revealed that more of the NETs-associated regulatory genes linked to poor cancer survival were associated with extracellular matrix (ECM) remodeling and pan-cancerous risk factors. SPP1 was found to be highly expressed and correlated with NET formation in cancers with poor survival. We also found that co-upregulation of NETs formation and SPP1 expression was closely linked to increased EMT and poor survival, that SPP1 influenced NET-induced malignant capacity, and that SPP1 overproduction induced robust formation of metastatic-promoting NETs. Conclusion NETs were common across cancers, but displayed a diverse regulatory pattern and outcome readouts in different cancer types. SPP1 is potentially the key to NETs-related poor outcomes.